Capacity building for sustainable use of animal genetic resources - Mpofu, N.; Ibrahim; Smalley, M.E.; Rege, J.E.O. (Bunda College of Agriculture, 2001)
Africa has a challenge to meet the rising food demands that will come about due to increased population size and urbanization. Such challenges can be tackled in many ways that include improving livestock production and this entails making improvements in feeding and disease control, using appropriate genotypes and genetic improvement of livestock. Research and training are some of the major requirements to realization of improvements in livestock production. Sub-Saharan Africa has a number of colleges and universities and research stations that do postgraduate training and do research in animal breeding and genetics. It is important that training and research at these institutions is relevant to Africa s needs so as to produce scientists that will become trainers or take up leadership in research and Development in animal breeding including sustainable use of animal genetic resources. The International Livestock Research Institute (ILRI) and the Swedish University of Agricultural Sciences (SLU) have initiated a capacity building project. This project aims to address training of researchers in animal genetic resources by introducing a new model of capacity building which targets qualified lecturers and researchers working in sub-Saharan African universities and research stations with a specific focus on making graduate training in sub-Saharan Africa more relevant to the region. The paper describes the project in terms of identified needs and expectations of stakeholders, the capacity building model developed to address these needs and the activities that are to be undertaken to meet the project outcomes. The project activities include a training of trainers course, building partnerships and developing computer-based training resources for use by university lecturers and national scientists. The proposed project evaluation procedures are also presented.